PROPOSAL OF INFRASTRUCTURE INFORMATION TECHNOLOGY FRAME WORK TOGAF FOR PAGAR ALAM TOWN GOVERNANCE - Buhori Muslim; Desi Puspita; Fatmayeni (LPPM UNIVERSITAS BINA INSAN, 2019)
Abstract The development of e-government is a long program planned by the Indonesian Government to be contained in Presidential Instruction number 3 of 2003 concerning national policies and strategies for e-government development, this is intended to realize or implement a bureaucracy that is reliable, professional, productive in excellent service to the community the purpose of implementing good governance, it must also be carried out by local governments such as the City of Pagar Alam, to achieve this desire management systems and work processes must be developed or utilized using Information and Communication Technology (ICT) facilities as needed, in this case Information Technology is the foundation the main support is that later all information systems will be able to provide services for the needs, for this expectation needs to be made good infrastructure planning, in this study used the TOGAF framework (The open group architecture framework) as a framework that there is a reference to the design of the information technology infrastructure of the Pagar Alam City Government, the results are: (a). 28 candidates were proposed to be developed, (b). It was concluded that the connection to each SKPD must be connected to fiber optic fiber using Metro-LAN or Metro-MAN, (c). Obtained the latest concepts and online community service systems, (d). From the analysis, it is known that the application and technology gaps must be repaired or replaced, which ones need to be maintained or integrated using the appropriate system.